SPECIFIC FEATURES IN THE BIOLOGY OF APHIDS (Scientific journal of the Fergana State University, 2024)
In this article, the specific features of ethological relations and behavioral reactions in the aphid population, ethological structure, as well as the variety of formation of the aphid colony were explained;Also, the main manifestations of behavioral reactions in aphids, i.e. aphids' feeding and habitat selection, swarm diversity, formation and re-formation, aphid protection, aphids' relationships with other insects, aphids' egg-laying and reproduction, adaptation characteristics of aphids to changing environmental conditions were interpreted.